The role of pharmacists in ensuring rational antibiotic therapy within the interdisciplinary team - Królak-Ulińska, Aneta; Religioni, Urszula; Chełstowska, Beata; Panford-Quainoo, Edwin; Doniec, Zbigniew; Vaillancourt, Regis; Merks, Piotr (Medicine and Pharmacy Reports, 2025)
The irrational use of antibiotics is one of the biggest threats to public health, as recently highlighted in the documents from the World Health Organization. It includes both the choice of an inappropriate drug, dose, form, or length of therapy for the patient, and a lack of attention to the global cost of treatment. One of the effects of excessive and irrational use of antibiotics worldwide is the increasing number of antibiotic-resistant microorganisms. The growing number of bacterial illnesses and deaths caused by this type of pathogens is of great significance, making the consequences of incorrect antibiotic use both medical and economic. In the rationalization of pharmacotherapy, the significant role of medical staff, including pharmacists, who have extensive knowledge in the field of antibiotic therapy, is emphasized. The main goal of the rational management of antimicrobial drugs should be to improve patient treatment outcomes and minimize the medical and economic consequences of antibiotic use. Antibiotic therapy rationalization programs are needed in all healthcare facilities, both in open care and in hospital settings. Educational interventions that target primary care physicians and physicians prescribing antibiotics in hospitals are necessary. Additionally, pharmacists, being the most accessible healthcare workers, can build awareness of rational antibiotic therapy among patients.